Peningkatan Pengetahuan dalam Pencegahan Hipertensi melalui Pendidikan Kesehatan dan Metode Demonstrasi - Laferani, Yuni; Setiyono, Andik (Universitas Pahlawan Tuanku Tambusai, 2025)
The rate of increase in new cases and the prevalence of hypertension are major health problems, both at the global, regional, and national levels. There are several causes of hypertension such as overweight/obesity, unhealthy diet, excessive sodium intake, insufficient potassium intake, insufficient physical activity, and alcohol consumption. The purpose of community service is to increase the knowledge of the Mangkubumi community about preventing hypertension by making low-salt vegetable salad. The method is carried out through providing health education and demonstrations on how to make vegetable salad. The media used are power point presentations, calendars containing information about hypertension. The results of this community service were tested using statistical tests with a dependent T test obtained p-value = 0.001, meaning that statistically there is a significant difference in knowledge between before and after health education and training were provided. Community service activities resulted in changes in the average value of respondents' knowledge of preventing and treating hypertension.